Safety and health at work management model for autonomous telework in Colombia (2020)
The results of this paper are determined by the guidelines and regulations applicable to teleworking in Colombia in terms of occupational health and safety, to the design of the Occupational Health and Safety Model for autonomous teleworking, and to the structuring and validation of the Maturity of the Occupational Health and Safety Management System (ema), Quality of Life (CoL), and Working Conditions (wc) instruments. For the development of the Model, the following categories were analyzed: advantages and disadvantages of teleworking, teleworking modalities, worker conditions, environmental conditions, conditions of the tasks, change management, leadership, and quality of life. Statistical validations were performed on each proposed instrument, such as internal consistency, factor analysis, and component analysis. In the proposed Model, the employer or contractor must address the prevention of accidents and occupational diseases and the protection and promotion of the health of workers and/or contractors through the implementation, maintenance, and continuous improvement of a management system with principles based on the pdca cycle (Plan, Do, Check, and Act).